2021
DOI: 10.13189/lls.2021.090401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flipped Learning Strategy on Developing Saudi University Students' English Reading Comprehension and Their Attitudes towards the Strategy

Abstract: Flipped Learning Strategy (FLS) has become one of the innovative trends in education to create an exciting learning environment where the instructor becomes a facilitator or guide and students construct their knowledge. Therefore, the current study aimed at investigating the effect of the Flipped Learning Strategy (FLS) on developing university students' English reading comprehension. The study also sought to reveal students' attitudes towards the use of the flipped learning strategy. The study sample consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Many studies (e.g., Albdour (2017), [1] Alghalban (2019), [4] Al-Shaigy (2016), [9] Al-Shedeiah (2014), [10] Al-Swelmyeen & Sakarneh (2020), [11] Amalia & Devanti (2016), [12] Azmi & Usman (2021), [13] Jabbaripour, Mostafaii, &Marefat (2017), [22] Joseph, et al, (2016), [23] and Bataineh& AL-Shbatat (2019)) [16] confirmed thatself-questioning strategy is advantageous and effective. Additionally, it was revealed that a small number of research studies had been conducted to look at howself-questioning strategy affected college and high school students' reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies (e.g., Albdour (2017), [1] Alghalban (2019), [4] Al-Shaigy (2016), [9] Al-Shedeiah (2014), [10] Al-Swelmyeen & Sakarneh (2020), [11] Amalia & Devanti (2016), [12] Azmi & Usman (2021), [13] Jabbaripour, Mostafaii, &Marefat (2017), [22] Joseph, et al, (2016), [23] and Bataineh& AL-Shbatat (2019)) [16] confirmed thatself-questioning strategy is advantageous and effective. Additionally, it was revealed that a small number of research studies had been conducted to look at howself-questioning strategy affected college and high school students' reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, integrating self-questioning strategy may improve students' reading comprehension skills. In the same line, many studies (e.g., Jabbaripour, Mostafaii, & Marefat, 2017; [22] Alghalban (2019); [4] Azmi and Usman, 2021) [13] found that self-questioning strategy had a positive effect and recommended it in the teaching/ learning process.…”
Section: Statement Of the Problemmentioning
confidence: 92%
See 1 more Smart Citation